“Developing Aesthetic Perception and Creative Approaches in Fine Arts Education at Higher Institutions” - Kodirov Obid Esonboy o‘g‘li (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines methods for developing aesthetic perception and fostering creative approaches in fine arts education at higher institutions. The study focuses on pedagogical strategies that combine observational analysis, project-based tasks, and multimedia tools to enhance students’ artistic literacy, critical thinking, and creative problem-solving skills. Emphasis is placed on practical techniques to engage students actively, promote independent exploration, and cultivate reflective learning in the visual arts.